2009
DOI: 10.1111/j.1541-1338.2009.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Regulated Community in Environmental Policy: The View from Below

Abstract: Discussions in environmental policy often focus on the highest levels of decision making and action while paying scant attention to those individuals on the front lines. Among those frequently overlooked are the individuals at regulated facilities who interact with government regulators on a frequent basis. Interviews with nearly two dozen facility personnel in Virginia yield findings that challenge common perceptions of the relationships between facility personnel and inspectors. In particular, 86 percent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Statistical testing indicates that these questions are reliable measures (Cronbach's α=0.844); factor analysis confirms their relationship. 17 Pautz (2009b) found that facility personnel in Virginia sought compliance as well and were far less resistant to the demands of environmental regulation, as may have been thought initially. The motives for compliance may not be environmental-further study is needed-but compliance is the goal according to these regulators.…”
Section: Evaluating Interactions With the Regulated Communitymentioning
confidence: 98%
“…Statistical testing indicates that these questions are reliable measures (Cronbach's α=0.844); factor analysis confirms their relationship. 17 Pautz (2009b) found that facility personnel in Virginia sought compliance as well and were far less resistant to the demands of environmental regulation, as may have been thought initially. The motives for compliance may not be environmental-further study is needed-but compliance is the goal according to these regulators.…”
Section: Evaluating Interactions With the Regulated Communitymentioning
confidence: 98%
“…Three-quarters, or 75%, identified as white males 9 is unsurprising given that the environmental science and engineering fields are dominated by men, both on the regulator side and regulatee side of the interaction, as others have found (cf. Pautz, 2009a;Pautz & Rinfret, 2013). Survey respondents typically have a high school degree or some college education, and are within the age range of 55-74.…”
Section: Overview Of Survey Respondentsmentioning
confidence: 99%
“…At this juncture, we might make sense of these results by saying regulators are fairly positive of their interactions with the regulated community, but are also cautious in their assessments of the regulated community because their job in the existing regulatory regime is to verify compliance and enforce the regulations when needed. Pautz (2009a, 2010) concludes that the interactions between regulators and the regulated community are far more positive than commonly presumed and May (2005) and Pautz (2009b) reach similar conclusions from the perspective of the regulated community. Nevertheless, further research is undoubtedly needed to more fully understand regulators' perceptions.…”
Section: Categorization Of Frontline Regulators' Perceptionsmentioning
confidence: 59%
“…However, at least in this limited sample, these perceptions appear to have evolved and OEPA regulators seem to think that the regulated community has at least the intention to comply, albeit for varying motives. Pautz (2009b) found that facility personnel in Virginia sought compliance as well and were far less resistant to the demands of environmental regulation as may have been thought initially. The motives for compliance may not be environmental—further study is needed—but compliance is the goal according to these regulators.…”
Section: Perceptions Of Frontline Regulators In Ohiomentioning
confidence: 99%